P138 The use of video capsule endoscopy (vce) in patinets with a new diagnosis of Crohn's disease: the experience of one center. (30th January 2023) - Nicolaou, P; Theodoropoulou, A; Psistakis, A; Arna, D; Velegraki, M; Fragkaki, M; Karmiris, K; Vardas, E; Paspatis, G
Abstract: Background: Crohn's disease can involve any segment of the gastrointestinal tract, with terminal ileum being the most common affected part. The wireless or video capsule endoscopy (VCE) is a valuable diagnostic tool in detecting lesions in the small bowel beyond terminal ileum. The findings of the procedure in combination with other clinical, endoscopic and laboratory factors can determine the therapeutic plan. Herein, we analyzed the findings of VCE in patients with suspicious or definite Crohn's disease, and assessed its contribution to the therapeutic plan. Methods: We evaluated these parameters in a retrospective analysis of 127 patients who underwent wireless capsule endoscopy in our department since June 2020. Results: 49/127 patients (51% male) were included in the study. The mean age was 40.24 years (SD ±14.30, IQR= 73–15). The majority of them (93.9 %) presented with a newly diagnosed Crohn's disease or terminal ileitis. The VCE examination was performed to detect any other lesions in the small bowel. 6.1% had chronic diarrhea without endoscopic findings. 57.1% had findings of Crohn's disease across the entire small bowel, 26.6% had sparse ulcers in the terminal ileum. In 12.2% multiple aphthous ulcers and edema were found in the terminal ileum and 4.1% had no findings. After VCE examination, initiation of treatment was considered in 57.1%. Magnetic enterography (MRE) was performed in 24.5% of the patients. VCE showed more extended lesions in the small bowel compared to MRE which showed non-specific terminal ileitis up to 15 cm in all patients. Conclusion: In patients with mild terminal ileitis wireless capsule endoscopy reveals extended lesions in the small bowel leading to adjustments in the therapeutic plan. In patients with newly diagnosed or suspected Crohn's disease, VCE can contribute to the assessment of the severity and location of the lesions as well as to the therapeutic plan.